Polityczność, polityka i Pan Nergal w kontekście tabloidyzacji polskiej sceny politycznej - Walecka-Rynduch, Agnieszka (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
The purpose of this paper is to analyze public discussion on the place of the artist Nergal in Polish society (or outside of this society). This discussion has significantly expanded the present context of the tabloidization of political stage and the dimension of politicality. As indicated by Chantal Mouffe, modern politicality is played out in the “moral register”. The conflict between “right and left” wing is replaced by the “struggle between good and evil”. Politicians have ‘used’ a private individual, or the artist-celebrity – Adam Darski, to create a powerful social dichotomy, dividing society into good, religious, Catholic believers who condemn the staged artistic expression of the Behemoth band and the bad, non-religious, non-Catholic non-believers who are indifferent to how religious symbols are used. What is peculiar is the fact that this discussion took place in the opinion-forming press on the one hand and in tabloids and gossip services on the other. This undoubtedly demonstrated the tabloid-like dimension of the Polish political stage, which has been observable for some time now, although all sides were convinced they were acting as a defender of Polish democracy.